PEMBAYARAN DIVIDEN DAN KUALITAS LABA PADA PERUSAHAAN KEUANGAN TERDAFTAR DI BEI - Yurika; Herman Ruslim (Jurnal Kontemporer Akuntansi, 2023)
The purpose of this study is to examine the relationship between dividend payment and earnings quality. This study examines four dividend features, they are dividend-paying status, dividend size, dividend changes and dividend persistence. Samples consist of 79 financial industries which listed in Indonesia Stock Exchange from 2015 until 2019. This study is using IBM SPSS Statistics software version 21 with GLM (Generalized Linear Model) research method. Result of this study showed that dividend-paying status, dividend size, dividend changes and dividend persistence have positive association with earnings quality. Overall, dividend-paying status, dividend size, dividend changes and dividend persistence are indicators for earnings quality.